Mitochondria-Associated Endoplasmic Reticulum Membranes in Breast Cancer - Yu, Hongjiao; Sun, Chaonan; Gong, Qing; Feng, Du (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria-associated ER membranes (MAMs) represents a crucial intracellular signaling hub, that regulates various cellular events including Ca2+ homeostasis, lipid metabolism, mitochondrial function, and cellular survival and death. All of these MAMs-mediated cellular events contribute to carcinogenesis. Indeed, altered functions of MAMs in several types of cancers have been documented, in particular for breast cancer. Over the past years, altered expression of many MAMs resident proteins have been reported in breast cancer. These MAM resident proteins play an important role in regulation of breast cancer initiation and progression. In the current review, we discuss our current knowledge about the functions of MAMs, and address the underlying mechanisms through which MAMs resident proteins regulate breast cancer. A fuller understanding of the pathways through which MAMs regulate breast cancer, and identification of breast cancer-specific MAMs resident proteins may help to develop novel therapeutic strategies for breast cancer.